Promoting organic nucleation of diclofenac: hydrophobic interfacial interactions drive self-assembly - Lu, Hao; Wiedenbeck, Eduard; Macht, Moritz; Qi, Daizong; Dhinojwala, Ali; Zuilhof, Han; Zahn, Dirk; Cölfen, Helmut; Bonn, Mischa (Chemical Science, 2025)
We compare the pH-triggered nucleation of the pharmaceutical diclofenac in bulk solution and at the air–water interface, using a combination of cryo-transmission electron microscopy, surface-specific spectroscopy and microscopy, and molecular dynamics simulations. In solution, simulation data reveal diclofenac forms dynamically ordered, liquid-like pre-nucleation clusters (PNCs), following a nonclassical nucleation pathway. At the air–water interface, nucleation occurs earlier during the titration process. The promoted nucleation is attributed to the interfacial enrichment of protons at this hydrophobic interface, elevated interfacial apparent pK a for diclofenac, as well as the interface-induced ordered diclofenac–water structures. While hydrophobic interactions drive the first air–diclofenac–water layer, further diclofenac molecules tend to separate from water by forming hydrogen-bonded dimers, characteristic of the crystal structure. These findings provide molecular-level insights into organic nucleation, highlighting the importance of hydrophobic interfaces in controlling the process, with potential implications for various applications in pharmaceutical and materials science.
CRIS-Team Scopus Importer:2025-10-24